(Dis)Education of the body through arts in the pedagogues preparation (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
The article approaches a proposal of studies in corporal practices that has been carried out in the Pedagogy course from combinations of elements of the Laban system, the Klauss Vianna Technique, the Viola Spolin´s theater games and the cultures of play, which generates multifocal approaches and broaden spaces in teachers´ education for the (mis)education of the oppressed body. Specificities of working with the body in this course are discussed and the relevance of multi-referentiality as a fruitful epistemological position in the body formation of professionals from the field of Education. The main conceptual bases that support the practices are presented in the form of a memorial, narrating about researchers, their techniques, didactics and methodologies. The artistic and didactic experiments are described, while their analyzes are designed through the dialogue between practices and theoretical substrates.
Keywords: Body; Pedagogy; Teacher education